Social Transfers and Deprivation in Ireland: A study of cash and non-cash payments tied to housing, childcare, and primary health care services - Maître, Bertrand; Privalko, Ivan; Watson, Dorothy (ESRI and the Department of Social Protection, 2020)
A ESRI study commissioned by the Department of Social Protection found that tied cash and non-cash transfers are associated with lower deprivation, especially among vulnerable families. The authors considered benefits tied to housing, childcare, and medical services using 2017 data.